Predominant generation of 15-lipoxygenase metabolites of arachidonic acid by epithelial cells from human trachea. - Hunter, J A (1985)
Epithelial cells of 99% purity and 92% viability were isolated from human tracheas obtained post mortem, and the cellular pathways for lipoxygenation of arachidonic acid were examined in vitro. The lipoxygenase metabolites were identified by comparison with synthetic standards during reversed-phase and straight-phase high-pressure liquid chromatography, UV spectroscopy, and gas chromatography/mass spectrometry. Epithelial cells incubated without arachidonic acid failed to generate detectable quantities of metabolites, while cells incubated with arachidonic acid at 1-50 micrograms/mf for 1-30 min invariably generated predominantly 15-lipoxygenase products, including 15-hydroxyicosatetraenoic acid (15-HETE), four isomers of 8,15-dihydroxyicosatetraenoic acid (two 8,15-diHETES and two 8,15-leukotrienes), at least one isomer of 14,15-dihydroxyicosatetraenoic acid, and smaller amounts of 12-HETE and 8-HETE, but little or no detectable 5-HETE or 5,12-diHETEs. The capacity of epithelial cells from human pulmonary airway to selectively generate 15-lipoxygenase metabolites of arachidonic acid suggests a potential role for the products as mediators of airway epithelial function.